USE OF ELECTRICAL NETWORKS WITH DISTRIBUTED GENERATION FOR BALANCED ELECTRICITY SUPPLY - Щербина, Дмитро (Modern engineering and innovative technologies, 2023)
This article is devoted to research and analysis of the use of distributed generation electric networks for balanced electricity supply. The main purpose of the article is to consider the benefits and challenges associated with changes in electrical netw